Customer requirement patterns for software vendors - Kousik, S.; Krishna, Aneesh (IEEE Computer Societ, 2013)
More and more electronics companies are outsourcing their hardware/software components. With a number of mergers and acquisitions, the number of available system software vendors is decreasing. The rising complexity in product features also places tremendous burden on each vendor to manage their requirements in such a way so as to cater to diverse requirements sets from various customers. As a result, it becomes imperative to pin down the requirements as early as possible in the development phase to ensure a greater chance of project success. This paper discusses a model that is based on requirements patterns. This model comprises of various requirements sets that focus on requirement aggregation and classification thereby managing high-level requirements in an efficient manner.